Manifestaciones visuales y oculares en niños usuarios de dispositivos electrónicos móviles en edad preescolar y escolar de 3 a 16 años, Medellín (2023)
Excessive consumption of mobile devices can affect proper neurological development and cause visual and behavioral damage in children and may be associated with visual dysfunction in adulthood.